SERVICE FACILITY ANALYSIS AND WORK ENVIRONMENT TO PASSENGER SATISFACTION LEVEL AT SULTAN HASANUDDIN INTERNATIONAL AIRPORT MAKASSAR - Pakki, Ibrahim; Nur, Nur Khaerat; Gusty, Sri (Universitas Ibn Khaldun Bogor, 2021)
Sultan Hasanuddin International Airport as one of the supporting sub-sectors of air transportation should be able to prepare and take strategic steps to proactively provide services and support customer needs for both airlines and passengers. This type of research is descriptive qualitative. The method of collecting data and information is Participatory Rapid Appraisal (PRA). Data analysis with statistical methods. The results showed that the physical facilities, the level of reliability of the officers, the responsiveness of the officers, the security guarantees, the attitude of the officers' empathy, the work environment at Sultan Hasanuddin Airport, showed a fairly small number of significance and had no effect on the level of passenger satisfaction. This can be interpreted that passenger satisfaction is quite good, but in this case to achieve a better value of passenger satisfaction, it is necessary to follow up so that the six variables get better attention so that the coefficient number is close to zero. It is recommended to improve both aspects of physical facilities and performance. The role of officers in serving passengers at Sultan Hasanuddin Airport Makassar.